Etika Penjualan dalam Perspektif Islam - Moh Nasuka (Muqtasid: Jurnal Ekonomi dan Perbankan Syariah, 2012)
Ethics is the orientation vehicle for human endeavor to answer a very fundamental question, how human should live and act, and many other questions. However, the reality has shown that no human can carry out their lives perfectly and satisfyingly. Ethical behavior in the utilitarian emphasis onpositivistic approach, but it ignores all aspects of the transcendental. Seculartheoriesinterpreted according to the desires and behaviors of the businessespeople, which have an impact on the failure of ethics in providing a meaningfulservice. Many cases of ethical violations performed by sales person affect alarge quantity of company losses. Islamic views on ethics are absolute ratherthan relative, it has a strong foundation based on principles of fairness andjustice, through the attitude of sidq, fatanah, amanah, tabligh. Whole seriesof activities in one’s life will be accountable before God